HUBUNGAN PENGETAHUAN DENGAN PERILAKU PENCEGAHAN PENYAKIT JANTUNG DAN PENCEGAHAN STUNTING DI SMAN 12 KONAWE SELATAN - hardiwa, enulia; Syahrianti, Syahrianti; Arsulfa, Arsulfa; Kartini, Kartini (Poltekkes Kemenkes Kendari, 2025)
Introduction: Heart disease is the leading cause of death for men, women, and people from most racial and ethnic groups. One person dies every 33 seconds from cardiovascular disease. The purpose of this study was to determine the relationship between knowledge and heart disease prevention behavior at SMAN 12 South Konawe. Methods: This study was quantitative and designed using an observational cross-sectional approach. The population was all 290 adolescents at SMAN 12 South Konawe, Lalembuu District, South Konawe Regency. The sample size was 74 adolescents. The instrument was a questionnaire. Data analysis used the chi-square test. Results: Of the 74 respondents, the majority of adolescents' knowledge was in the poor category (35 respondents (47.3%), and the majority of respondents (52 respondents (70.3%) did not engage in heart disease prevention behavior. The data analysis results obtained an X2 value of 9.032 (greater than the X2 table value of 5.99) and a p-value of 0.011 (? 0.05), thus concluding that there is a relationship between adolescent knowledge and heart disease prevention behavior at SMAN 12 South Konawe. Conclusion: There is a relationship between knowledge and heart disease prevention behavior at SMAN 12 South Konawe.